Social and Cultural Aspect in Foreign Language Motivation defined by Integrative and Instrumental Factors - Softa, Valbona (European Journal of Sustainable Development, 2019)
This paper aims to investigate the social and cultural aspect in foreign language learning motivation, with main focus English language, as a compulsory course in the official education curricula in Albania, from primary level to Master`s Study Programs. The indicators in this study are the integrative and instrumental variables. Based on the literature review and empirical research data, two research questions are presented in this paper: 1. At what extent are students motivated to learn English language in terms of integrative and instrumental orientation? 2. Which factor is the best predictor to motivation in English language learning? A quantitative method was approached and data was analyzed through SPSS, 18. Attitude Motivation Test Battery was applied in a sample of 1800 subjects. The reliability Alfa Chronbach coefficient of the Test was (=.88). The findings showed that best predictor variable to motivation in language learning is the integrative factor, at values ß=0.476, t=21.110. Students motivation is also positively varied from the instrumental language orientation, (ß = .302, t=16.919. This result is statistically significant, p<0.001. The study also found that students are moderately motivated to learn the language because of integrative reasons, mean value (M=5) out of a Likert scale (1- 6), SD=0.86; the students are only slightly motivated in terms of language Instrumental orientation, mean value (M=4.2) out of (6), SD= 0.1. Keywords: integrative language orientation, instrumental language orientation, motivation to learn English